STRATEGI DAN DINAMIKA MANAJEMEN INTERNASIONAL DALAM LEMBAGA PENDIDIKAN MODERN - Dendi Eriyan Ihza Nakazima; Bahrani; Sudadi (STKIP Subang, 2026)
In the era of globalization, modern educational institutions are faced with the demand to transcend national boundaries through integrated internationalization strategies. This study aims to analyze the strategies and dynamics of international management in modern educational institutions in Indonesia in an effort to maintain global competitiveness. Using a qualitative approach with a literature study method, this study examines several primary references consisting of accredited scientific journals and educational management textbooks. The results show that effective primary strategies include strengthening cross-border strategic alliances, standardizing quality based on international accreditation, and accelerating digitalization through an integrated learning management system. The dynamics found include administrative regulatory barriers, the need to adapt Human Resources competencies that are sensitive to cultural diversity, and challenges in implementing the concept of